Kemampuan Berfikir Kritis Dalam Pembelajaran Matematika Ditinjau dari Self Efficacy - Eva Risdianah; Ulum Fatmahanik (UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
The ability to think critically in learning mathematics is very important because it can make it easier for students to understand content, analyze concepts, plan calculation strategies and provide appropriate conclusions. But in fact, students' critical thinking skills are still not optimal due to lack of confidence (self-efficacy) in solving problems. Different students' self-confidence causes different students' critical thinking abilities. The purpose of this study was to describe the critical thinking skills of fifth grade students at SDN Kutukulon on speed and discharge in terms of high, medium, and low self-efficacy. The research method in this study used descriptive qualitative data collection techniques using questionnaires, tests and interviews. The results of the study show that: 1) Students with high self-efficacy fulfill 4 indicators namely interpretation, analysis, evaluation, and inference. However, there are weaknesses in the interpretation indicators where students are incomplete in writing information according to the context of the questions. 2) Students with moderate self-efficacy fulfill indicators of interpretation and analysis. While the evaluation and inference is quite good. This is because students only write down concepts without explanation and at the end of the answers are not equipped with a unit of account. 3) Students with low self-efficacy only meet 2 indicators, namely interpretation and analysis, while the evaluation and inference indicators are still not fulfilled because students make mistakes in counting so that the conclusions given are not appropriate according to the context of the questions given